Clinical relevance of endoscopic three‐dimensional imaging for quantitative assessment of phonation. (14th March 2018) - Semmler, Marion; Döllinger, Michael; Patel, Rita R.; Ziethe, Anke; Schützenberger, Anne
Abstract : Objective/Hypothesis: Laser‐based three‐dimensional (3D) imaging allows realistic visualization and absolute measurement of the vocal folds for comprehensive characterization of the oscillation pattern. Study Design: Exploratory study with descriptive data analysis in healthy cohort. Methods: The custom‐developed miniaturized measuring device is an endoscopic camera‐laser setup for stereo triangulation and suitable for in vivo application. The laser projection unit generates a regular laser grid that is projected on the vocal folds and recorded at 4000 fps using a high‐speed camera. Recordings are performed during sustained phonation on 10 healthy subjects. Results: We present absolute values for the lateral and vertical displacement amplitudes and maximum velocities during opening and closing phase. On average over all study participants, the vertical parameters are at least 50% higher than their lateral counterparts. The mean male/female amplitudes are 0.93 mm/0.80 mm in the lateral and 1.28 mm/1.45 mm in the vertical direction. Only 20% of the healthy subjects displayed slight asymmetries in the lateral direction, but 70% showed significant asymmetries in the vertical component. In only 30% of all subjects, the asymmetry trends matched in the lateral and vertical direction. Conclusions: The study illustrates the additional benefit of 3D imaging: consideration of the vertical component and computation of metric units. New, relevant, and even unexpected information was obtained by the incorporation of the additional vertical dimension. Metric units allow for an absolute evaluation of anatomy and dynamics and therefore enables cross‐study comparability. The noninvasive acquisition of quantitative measures for evidence‐based medicine has the potential to enhance diagnostic and therapeutic procedures as well as basic medical research. Level of Evidence: 4. Laryngoscope, 128:2367–2374, 2018